Impulse buying and lifestyle towards spending habits among youth in Pasir Gudang, Johor / Nurul Ain Mohd Zainorin - Mohd Zainorin, Nurul Ain (2019)
Spending habits has been one of the most researched topics in a variety of fields. This research aims to the spending habits among youth at Taman Kota Masai Pasir Gudang, Johor. The dependent variable is the elements of spending habits. Thus, our research is to study the relationship and significance of the dependent and independent variable. The purposes of this study are to identify the relationship impulse buying with spending habits and to identify the relationship lifestyle with spending habits. This study investigated using a questionnaire survey to the 217 respondents. This study also investigated using a questionnaire survey that is divided into 4 sections. Section A deals with questions on demographic background of respondents, Section B deals with question on spending habits, Section C deals with question on impulse buying and Section D deals with question on lifestyle. The results revealed that the spending habits with a mean value at (mean =5.3180), impulse buying (mean=4.7419} and lifestyle (mean=S.8157). The finding also depicts that there are significant relationship between spending habits of youth with impulse buying and lifestyle.